If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 11x + -7 Reorder the terms: 5y = -7 + 11x Solving 5y = -7 + 11x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = -1.4 + 2.2x Simplifying y = -1.4 + 2.2x
| 3(x+5)-2=6x-3(-4+x) | | -8x+3=25 | | 5y=11x+7 | | LNx=-1.6 | | Log(8x-7)/log(x) | | -6f+13=-9z+24 | | 9(5+x)=8(x-4) | | 5+2X=14-4N | | 4y-13=43 | | -8b/5=-1 | | 4x-38=9x-3 | | 5x+39=154 | | 6+65x=52x+18 | | x-5x^(1/2)-6=0 | | 2.6(x-0.8)=9 | | 7(y+6)=3+6y | | 6+65x=52+18 | | x^2+21x+30=9x+3 | | 112x+6=5x | | t/4-6=9 | | x/6-2/7=6 | | 5(b-4)=6(3+b) | | 2sin^2x=1-sinx | | |x/3-4|0 | | x^2-2x-14=10 | | (15x-4x)-(10-x)= | | 35y+6=61 | | 6x-2x-5=6+21 | | a/3+3=9 | | 63-4x=12-9x | | 9x-6x-5x+6= | | 5x+6=54 |